Kampus Mengajar : Tingkatkan Literasi Dan Numerasi Melalui Program Pelita Nusa Di SDN Tembok Dukuh III/85 Surabaya - Alifiarisma Maricar (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The Teaching Campus Program is part of the Merdeka Campus program which involves students from various tertiary institutions and various educational backgrounds to participate in helping the teaching and learning process as an effort to equalize education which needs to be addressed after witnessing the Covid-19 pandemic. Equity and improvement of the quality of education are citizens' rights that must be fulfilled by the government which are included in the TPB/SDGs. The Teaching Campus also provides opportunities for students to be directly involved and develop themselves through activities outside of lectures. The Teaching Campus is used as a forum for students to contribute to improving student literacy and numeracy from an early age, starting from the elaboration of elementary school to high school. Where later students are required to create creative innovations in supporting interactive learning by creating teaching program ideas. One of them is the Pelita Nusa Program which was created from students participating in the Teaching Campus 5 program who served at Tembok Dukuh III/85 Elementary School in Surabaya. This research was made in accordance with the facts according to reports and activities that have been carried out by female students to implement the Pelita Nusa program at Tembok Dukuh III/85 Elementary School in Surabaya